IMPLEMENTASI STRATEGI THINK-TALK-WRITE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X AKUTANSI PADA MATA PELAJARAN AKHLAK TARIKH DI SMK MUHAMMADIYAH 2 PONTIANAK - Bustami Bustami (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
One of the efforts to improve the quality of education and teaching is by choosing a strategy in delivering subject matter in order to obtain an increase in student learning achievement, especially in Tarikh Tarikh lessons, where some of this subject material will be implemented using the Think Talk Write learning strategy. The reason the researcher took the Akhlaq Tarikh lesson was because the facts in the field were shown by the results of the mid-semester exam for class 70 and above. Meanwhile, the learning completeness score (KKM) is 70. A similar thing also happened in previous years. The aim of this research is to obtain information and describe: 1) Implementation of the Think-Talk-Write strategy in learning Tarikh Morals in class X Accounting at SMK Muhammadiyah 2 Pontianak. 2) Improved student learning outcomes in the Tarikh Morals subject in class X Accounting at SMK Muhammadiyah 2 Pontianak. 3) the results of the Think Talk Write strategy in improving the learning outcomes of class In research, researchers use descriptive methods, namely research that describes or depicts the condition of the subject or object of research. The results of this research can be concluded that: student learning outcomes using the Think-Talk-Write Strategy in learning Tarikh Morals at SMK Muhammadiyah 2 Pontianak are said to be very good and have experienced significant improvement, this can be seen from observation data on student learning outcomes. There were pre-cycle learning outcomes with an average of 65.90%, students who achieved the KKM were 51%, and students who did not reach the KKM were 41%. In the first cycle, student learning outcomes increased significantly with an average of 66.82%, 63.63% of students who achieved the KKM, and 36.36% of students who did not achieve the KKM. and in cycle II student learning outcomes averaged 70.46, students who reached the KKM were 81.81%, and students who did not reach the KKM were 18.18%. Thus, student learning outcomes using the Think-Talk-Write Strategy have increased. The suggestion from this research is that it is hoped that the Think-Talk-Write learning strategy can be applied continuously in learning activities.